Improving the letter-writing method persuasive education in employees state 7 Medan middle school (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The problems of Indonesia, especially correspondence in the cases of standardized punctuation marks, vocabulary, and sentences according to Indonesian principle is presented, including effective letter format in the public service program. The people should take care of Indonesian properly and accurately, especially in a formal or official condition at schools or offices. In this case, the team of public service provided training for the employees at SMP Negeri 7, Medan to foster and development of Indonesian in correspondence so that they will be able to write letters accurately and effectively. The implementation used lecture and explanation method in teachers-students direct interaction; the trainers explained standard sentences, words, and spelling according to Indonesian spelling through LCD media. By using persuasive and educative method, the trainers asked the trainees to practice writing letters so that there was two-way communication which made them enthusiastic in participating the training. Many of them asked questions and were interested in following the program. In the post-exercise, most of them could get much more input. The result was that the employees could write letters effectively and accurately.